Online Travel Agent for Tourism System Using Big Data and Cloud - FAJAR, Ahmad Nurul; NURCAHYO, Aldian; QOMARIYAH, Nunung Nurul (Journal of Environmental Management and Tourism; Vol 11 No 2 (2020): JEMT Volume Xi Issue 2(42) Spring 2020, 2020)
Nowadays, more and more people can enjoy fast internet access that can be used for various activities such as browsing, shopping online, video calls, playing games and so on. Businesses are also utilizing this very rapid increase in internet technology. They sell products and services through the internet with various attractive offers and competing with each other to increase their sales. One strategy that can be done to get more sales is through the method of personalizing services for customers. The personalization aspect in e-tourism has been predicted to increase. Customers who are making valuable data at every stage of their journey are making a challenge for travel companies to collect and link these data points to improve their customer experience. Learning the customer behaviour can be very significant for Online Travel Agent. Because collecting millions of search results through their services and provide a smart travel experience, Online Travel Agent in Indonesia must use Big Data and Cloud technology alignment to win the competition in the market. The entire data lifecycle must be simple because of the needs of users to keep batch ingesting a lot of data likes once in an hour. Streaming analytics has grown over the past few years, it has become one of the most critical components of most of the businesses. We proposed Online Travel Agent (OTA) for Tourism System Using Big Data and Cloud.